Analysis Using Region’s Financial Accounting Information System on the Quality of Local Government Finance Reports - Zulkfli Fachri; Mediaty Mediaty (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
This study aimed to analyze the use of region’s financial accounting information system to the quality of local government financial reports. The quality of the financial statements include the relevance, reliable, comparable, and understandable. The dependent variable in this study is the quality of local government financial reports, while the independent variable in this study is the region’s financial accounting information system. This research method is qualitative research with this type of approach theoretical studies that the methods used to collect data or resources related to the topics in a study. Data obtained from journals, thesis,books , and various other literature related to the study. The results showed that the use of local financial information systems positive effect on the quality of local government financial reports.